New horizon for psychotherapy : autonomy as a profession - Holt, Robert R., 1917- (New York (N.Y.) : International universities press, 1971)
"Most of the chapters had their origins in a set of working papers prepared for an interdisciplinary conference on an ideal training program for psychotherapists ... which took place in 1963 at New York University's Frank Jay Gould House."